Parkinson-related parkin reduces α-Synuclein phosphorylation in a gene transfer model - Khandelwal, Preeti J (BioMed Central, 2010)
BACKGROUND: α-Synuclein aggregates in Lewy bodies and plays a central role in the pathogenesis of a group of neurodegenerative disorders, known as "Synucleinopathies", including Parkinson's disease. Parkin mutations result in loss of parkin E3-ubiquitin ligase activity and cause autosomal recessive early onset parkinsonism. RESULTS: We tested how these two genes interact by examining the effects of parkin on post-translational modification of α-Synuclein in gene transfer animal models, using a lentiviral gene delivery system into the striatum of 2-month old male Sprague Dawley rats. Viral expression of wild type α-Synuclein caused accumulation of α-Synuclein and was associated with increased cell death and inflammation. α-Synuclein increased PLK2 levels and GSK-3β activity and increased the levels of phosphorylated α-Synuclein and Tau. Parkin co-expression reduced the levels of phosphorylated α-Synuclein and attenuated cell death and inflammation. Parkin reduced PLK2 levels and increased PP2A activation. CONCLUSIONS: These data suggest that parkin reduces α-Synuclein levels and alters the balance between phosphatase and kinase activities that affect the levels of phosphorylated α-Synuclein. These results indicate novel mechanisms for parkin protection against α-Synuclein-induced toxicity in PD.